Consumo midiático, interculturalidade e cidadania: experiências de educadores e educadoras de escolas públicas no contexto da fronteira Brasil-Venezuela - Clemente, Sabrina Cancoro Generali (2023)
The objective of this thesis is to analyze media consumption experiences of male and female educators, as well as their implications, into the perspective of promotion and exercise of the citizenship and interculturality into schools of Boa Vista’s (RR) educational system, located in a border context, with a significant migratory presence of Venezuelans. This thesis is based on theoretical relations between communication, education, consumption and interculturality. The qualitative methodology of this research comprises exploratory research in schools and out of school’ spaces (digital and physical), semi-structured interviews with educators, open interviews with a government employee of the Secretary of Town for Education and Culture of Boa Vista (Secretaria Municipal de Educação e Cultura de Boa Vista, SMEC) and members of non-governmental organizations, furthermore referencing bibliographical and desk research. As results, within the scope of media consumption by educators, the criminalization of immigration in the media – especially in Boa Vista’s local media – reinforces xenophobia and aporophobia on the Venezuelan population residing in the capital of Roraima, reflecting into the speeches of the school community, including children, who tend to reproduce prejudiced speeches and practices. The immigrant is observed as the central axis of a involuntarily imported crisis from the neighboring country, an idea which was widely spread into political speeches during 2020 and 2022 electoral campaigns. The perception about the temporary nature of the migratory presence in the local context and in school spaces acts as a reinforcement of an assimilationist perspective towards immigrants and as an obstacle to the development of intercultural educational policies, despite the city of Boa Vista having a growing immigrant population since mid-2010s.